2012
DOI: 10.1121/1.4733557
|View full text |Cite
|
Sign up to set email alerts
|

The effect of interaural differences in envelope shape on the perceived location of sounds (L)

Abstract: Users of bilateral cochlear implants and a cochlear implant combined with a contralateral hearing aid are sensitive to interaural time differences (ITDs). The way cochlear implant speech processors work and differences between modalities may result in interaural differences in shape of the temporal envelope presented to the binaural system. The effect of interaural differences in envelope shape on ITD sensitivity was investigated with normal-hearing listeners using a 4 kHz pure tone modulated with a periodic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…It is therefore suggested that a perceptually relevant threshold level is in the order of À30 to À10 dB re peak, and not, as in previous studies, at À50 dB or lower. The proposed range is in line with the critical modulation depth (Stellmack et al, 2005) mentioned in the introduction and also with results from Francart et al (2012), suggesting that the binaural system puts more weight on higher level portions of the attack flank than on lower level portions.…”
Section: Discussionsupporting
confidence: 78%
“…It is therefore suggested that a perceptually relevant threshold level is in the order of À30 to À10 dB re peak, and not, as in previous studies, at À50 dB or lower. The proposed range is in line with the critical modulation depth (Stellmack et al, 2005) mentioned in the introduction and also with results from Francart et al (2012), suggesting that the binaural system puts more weight on higher level portions of the attack flank than on lower level portions.…”
Section: Discussionsupporting
confidence: 78%
“…Recent studies indicate that the main factors determining envelope ITD sensitivity are temporal properties of the envelope, such as the steepness of the onsets and the duty cycle Trahiotis 2009, 2010;Ewert et al 2009;Francart et al 2012;Laback et al 2011). Generally, ITD sensitivity improves with increasing onset steepness and increasing dead time, which is the time the envelope remains at the minimum level in every period.…”
Section: Introductionmentioning
confidence: 99%
“…Monaghan et al (2013) compared their results of the influence of attack time in similar stimuli to those reported in Chapter 2, finding them to be in line. Francart et al (2012) used the extended NCC model with adaptation loops, and were able to qualitatively account for their data. Recently, I developed and conducted a psychophysical experiment that measured the influence of selected envelope segments on the extent of laterality (Dietz et al, 2015).…”
Section: Chapter 5 General Conclusionmentioning
confidence: 99%